Suppose that we are trying to prove that for every positive integer n, if x and y are positive integers with max(x, y) = n, then x = y. For the base case, we suppose n = 1. If max(x, y) = 1 and x and y are positive integers, we have x = y = 1. Now we let k be a positive integer, and assume that whenever max(x, y) = k and x and y are positive integers, then x = y. Let max(x, y) = k + 1, where x and y are positive integers. Then max(x - 1, y - 1) = k, so by the inductive hypothesis, x - 1 = y - 1, so x = y. What is wrong with this ``proof''?
- Anybody can ask a question
- Anybody can answer
- The best answers are voted up and rise to the top
Are you familiar with the proof that all horses are the same color? Try googling that phrase, it fails in a similar (but not identical) way. Try working through the case $k=1$ of your problem, and think about what might go wrong with $x$ and $y$ when you try to apply your base case.